Generating Buoyancy in a Sea of Uncertainty: Teachers Creativity and Well-Being During the COVID-19 Pandemic - Anderson, Ross C.; Bousselot, Tracy; Katz-Buoincontro, Jen; Todd, Jandee (Frontiers in Psychology, 2021)
The global coronavirus disease 2019 (COVID-19) pandemic has caused significant uncertainty for students and teachers. During this time, teacher and student creative beliefs and affect play a supportive role in adaptively managing stress, finding joy, and bouncing back from inevitable setbacks with resilience. Developing an adaptive orientation to creativity is a critically important step in helping teachers deal with the challenges and stress of reaching their students through distance learning, especially the most marginalized. This study aims to understand how teacher creativity linked to well-being in the face of COVID-19-related school shutdowns and how teachers planned to adapt creatively to distance learning through the guidance of a summer creative teaching training institute. Results from this sequential mixed method study demonstrated important relationships. Creative self-efficacy in teaching related to teacher buoyancy in the face of setbacks. Creative growth mindset related to teachers’ general positive affect in teaching. Lowered creative anxiety related to reduced effects of secondary traumatic stress and general negative affect in teaching. Environmental support and encouragement for creativity in schools may be foundational for teacher well-being by enhancing teachers’ dispositional joy, general positive affect, and reducing general negative affect. Results suggested additional stress and loss of creativity for most teachers due to the COVID-19 pandemic alongside substantial capacity for creative adaptations with the support of training for creativity in teaching and learning.